Absconding among admitted patients with bipolar affective disorder diagnosis in Uganda - Joan Abaatyo; Alain Favina; Mark Mohan Kaggwa (BMC Psychiatry, 2023)
Abstract Background Hospitalization is often necessary for individuals with Bipolar affective Disorder (BAD) during severe manic or depressive episodes, as well as for stabilizing treatment regimens. However, a significant proportion of patients admitted for treatment of BAD abscond or leave the hospital without permission during their stay. In addition, patients managed for BAD may have unique characteristics that might force them into absconding. For example, the high prevalence of co-morbid substance use disorder – craving to use substances, suicidal behaviors – attempts to die by suicide, and cluster B personality disorders – characterized by impulsive acts. It is, therefore, essential to understand the factors contributing to absconding among patients with BAD, to facilitate designing strategies for preventing and managing this behavior. Method This study was based on a retrospective chart review of the inpatients diagnosed with BAD at a tertiary psychiatry facility in Uganda from January 2018 to December 2021. Results Approximately 7.8% of those with BAD absconded from the hospital. The likelihood of absconding among those with BAD increased with the use of cannabis [adjusted odds ratio (aOR) = 4.00, 95% confidence interval (CI) = 1.22–13.09, p-value = 0.022] and having mood lability [aOR = 2.15, 95% CI = 1.10–4.21, p-value = 0.025]. However, receiving psychotherapy during the admission (aOR = 0.44, 95 CI = 0.26–0.74, p-value = 0.002) and treatment with haloperidol (aOR = 0.39, 95% CI = 0.18–0.83, p-value = 0.014) reduced the likelihood of absconding. Conclusion Absconding among patients with BAD is common in Uganda. Those with symptoms of affective lability and those with comorbid cannabis use tend to abscond more, while those who receive haloperidol and psychotherapy are less likely to abscond.